(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2024)
This article talks about the methodology of teaching English, the use of modern technologies in learning foreign languages, the role and effect of gamification in language learning.In this article, we will explore the benefits of gamification in English language learning, how to implement gamification in the classroom, the challenges and limitations of gamification, and tips for successful implementation.